Alterations in neuromuscular function in girls with generalized joint hypermobility. Issue 1 (December 2016) - Jensen, Bente; Sandfeld, Jesper; Melcher, Pia; Johansen, Katrine; Hendriksen, Peter; Juul-Kristensen, Birgit
Abstract Background Generalized Joint Hypermobility (GJH) is associated with increased risk of musculoskeletal joint pain. We investigated neuromuscular performance and muscle activation strategy. Methods Girls with GJH and non-GJH (NGJH) performed isometric knee flexions (90°, 110°, 130°), and extensions (90°) at 20 % Maximum Voluntary Contraction, and explosive isometric knee flexions while sitting. EMG was recorded from knee flexor and extensor muscles. Results Early rate of torque development was 53 % faster for GJH. Reduced hamstring muscle activation in girls with GJH was found while knee extensor and calf muscle activation did not differ between groups. Flexion-extension and medial-lateral co-activation ratio during flexions were higher for girls with GJH than NGJH girls. Conclusions Girls with GJH had higher capacity to rapidly generate force than NGJH girls which may reflect motor adaptation to compensate for hypermobility. Higher medial muscle activation indicated higher levels of medial knee joint compression in girls with GJH. Increased flexion-extension co-activation ratios in GJH were explained by decreased agonist drive to the hamstrings.